The Construction of Ethnic Discrimination in the Pengepungan Di Bukit Duri Film - Aureno Putra Wicaksono; Ade Kusuma (International Journal of Social, Economic, and Business, 2026)
Set in a dystopian future in 2027, the film Pengepungan di Bukit Duri portrays a bleak reality in which the Chinese ethnic group is trapped in a vortex of systemic racism and social exclusion. Film is a form of mass media that not only serves to convey information but also shapes social reality through audio and visual elements that can influence viewers' perceptions. It also becomes a medium for constructing ethnic discrimination, where ethnic identity becomes a determinant of an individual's social position and security. This study aims to examine the representation of ethnic discrimination in the film through the analysis of narratives of othering, scapegoating, and the rejection of minority authority, using a descriptive qualitative method with Roland Barthes’ semiotic analysis approach. The results show that Pengepungan di Bukit Duri depicts the Chinese ethnic group as foreigners or the other, despite having been settled for generations, positioning this minority group as vulnerable targets or scapegoats for the outpouring of social frustration amid a national crisis. This research also explains that the film serves as a sharp social critique of the fragility of an inclusive society, and provides a space for critical reflection to challenge racial prejudices that are passed down to younger generations.